2010 IEEE 4th International Conference on Internet Multimedia Services Architecture and Application 2010
DOI: 10.1109/imsaa.2010.5729414
|View full text |Cite
|
Sign up to set email alerts
|

A scalable location-based services infrastructure combining GPS and Bluetooth based positioning for providing services in ubiquitous environment

Abstract: Several methodologies on the provisioning of the Location-Based Services (LBSs) solely using GPS-based positioning or combining several positioning techniques like GPS, GSM Cell-ID, Wi-Fi, Bluetooth and RFID etc. have been proposed over the past few years. Most of these systems do not focus on limited battery power, memory-constraint of the mobile devices, the heterogeneity of mobile platform and proper authentication checks before providing LBSs to the mobile user. Our proposed system utilizes low-cost, low-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…By formulating the optimization problems as linear programs, the authors showed how to find the optimal LPPMs considering the user's requirements on both location privacy and service quality. [29][30][31] A new location privacy framework that generalized the well-known differential privacy model in statistical database through geoindistinguishability. The major difference of geoindistinguishability from the previous 2 frameworks is that it abstracts away the prior knowledge of the adversary.…”
Section: Location Privacy Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…By formulating the optimization problems as linear programs, the authors showed how to find the optimal LPPMs considering the user's requirements on both location privacy and service quality. [29][30][31] A new location privacy framework that generalized the well-known differential privacy model in statistical database through geoindistinguishability. The major difference of geoindistinguishability from the previous 2 frameworks is that it abstracts away the prior knowledge of the adversary.…”
Section: Location Privacy Modelmentioning
confidence: 99%
“…The major difference of geoindistinguishability from the previous 2 frameworks is that it abstracts away the prior knowledge of the adversary. The work extended 31 by optimizing the quality of service while satisfying geoindistinguishability. Besides location privacy models, many concrete location privacy protection mechanisms (LPPMs) have been proposed in the past few years.…”
Section: Location Privacy Modelmentioning
confidence: 99%
“…In the past decade, outdoor positioning technology and research in this area have shown explosive growth in achievement [2,[6][7][8][9][10][11][12][13]. At the moment, similar trends are observed for indoor positioning technologies, and it can be noted that indoors people spend more than 70% of their lives.…”
Section: Review Of Existing Approaches To the Development Of Geographic Information Positioning Systemsmentioning
confidence: 90%
“…The problem of indoor positioning has been discussed in articles since 1994. A comprehensive picture of the current situation is given in the articles of 2007-2014 [1][2][3][4][5][6][7][8][9][10][11][12]. For example, Davide Dardari, Pau Closas and Petar M. Djuric [1] have shown that for all existing technologies of radio frequency positioning and positioning by using separate sensors of speed, earth magnetic field and acceleration, the maximum achievable accuracy is tens of centimeters at a significant cost.…”
Section: Review Of Existing Approaches To the Development Of Geographic Information Positioning Systemsmentioning
confidence: 99%
See 1 more Smart Citation